Demographic Aspects of Migration
350 p. 52 illus.
Keywords: In all settings of society, migration is an important factor for the development and growth of population. To understand its consequences, it is fundamental to know the quality of the available data, the measurement instruments for analyzing migration, and to have an appropriate demographic framework for studying the demographic effects of migration. Whereas the first section focuses on analysis, the second part deals with the different demographic behaviours of migrants compared to residents. Further it demonstrates the motives and explanations for migration. The final section analyzes geographic and economic aspects. The authors combine demographic analysis, interdisciplinary research, and international illustrations to explore current trends in migration patterns and processes. This book is valuable reading for an interdisciplinary academic audience as well as for regional planners and policy makers.